Divergent metabolic responses dictate vulnerability to NAMPT inhibition in ovarian cancer. Issue 9 (26th January 2020) - Kudo, Kei; Nomura, Miyuki; Sakamoto, Yoshimi; Ito, Shigemi; Morita, Mami; Kawai, Masaaki; Yamashita, Yoji; Ito, Kiyoshi; Yamada, Hidekazu; Shima, Hiroshi; Yaegashi, Nobuo; Tanuma, Nobuhiro
Abstract : It is of current interest to target cancer metabolism as treatment for many malignancies, including ovarian cancer (OVC), in which few druggable driver mutations have been identified. Nicotinamide phosphoribosyltransferase (NAMPT), a rate‐limiting enzyme in the NAD salvage pathway, is a potential therapeutic target in OVC. However, factors that determine responsiveness to NAMPT inhibition are not fully understood. Here, we report that OVC cell lines can be divided into subgroups exhibiting NAMPT‐dependent or NAMPT‐independent glycolysis, and these metabolic differences correlate with vulnerability to NAMPT inhibition. Interestingly, cells showing NAMPT‐dependent glycolysis were enriched in a group of cells lacking BRCA1/2 gene mutations. Our findings suggest the importance of selecting appropriate patients for NAMPT‐targeting therapy in OVC. Abstract :